Perception of Supports and Barriers: Career Decision-Making for Sikh Indo-Canadian Young Women Entering the Social Sciences - Mani, Priya S. (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this research study was to examine the supports and barriers that Sikh Indo-Canadian young women perceive in their career decision-making process to enter the applied social sciences at the university level. A qualitative descriptive case study approach (Yin, 2003) was used. Analyses indicated self-efficacy appraisals played an important role in moderating the participants’ views of supports and barriers in their career decision-making processes. Implications for career counsellors are discussed.